The Effect of Company Characteristics and Cooperate Social Responsibility on Company Financial Performance - ZA, Zahroh; Suhadak, Suhadak; Saifi, Muhammad; Firdausi, Nila (JPAS (Journal of Public Administration Studies), 2020)
Increased intense global competition has made CSR as a topic that must be considered by business people, especially for companies that carry out activities related to natural resources. The rationality for this statement is that CSR has become one of the company's responsibilities to stakeholders, and company characteristics are an inherent risk inherent in the company. All of this is related to the company's financial performance. Various previous studies have been conducted to discuss the effect of company characteristics and CSR on company financial performance, but give different results. The purpose of this study was to obtain empirical evidence of the influence of company characteristics and CSR on the financial performance of companies listed on the Indonesia Stock Exchange (BEI) in 2012-2016. The study population was natural resource companies listed on the BEI 2012-2016 of 43 companies, with through specific criteria obtained a sample of 32 companies. The results showed that company characteristics significantly influence the company's financial performance as well as CSR significantly influence the company's financial performance.